Infiltration from the Pedon to Global Grid Scales: An Overview and Outlook for Land Surface Modeling. Issue 1 (24th June 2019) - Vereecken, Harry; Weihermüller, Lutz; Assouline, Shmuel; Šimůnek, Jirka; Verhoef, Anne; Herbst, Michael; Archer, Nicole; Mohanty, Binayak; Montzka, Carsten; Vanderborght, Jan; Balsamo, Gianpaolo; Bechtold, Michel; et al.
Abstract : Core Ideas: Land surface models (LSMs) show a large variety in describing and upscaling infiltration. Soil structural effects on infiltration in LSMs are mostly neglected. New soil databases may help to parameterize infiltration processes in LSMs. Infiltration in soils is a key process that partitions precipitation at the land surface into surface runoff and water that enters the soil profile. We reviewed the basic principles of water infiltration in soils and we analyzed approaches commonly used in land surface models (LSMs) to quantify infiltration as well as its numerical implementation and sensitivity to model parameters. We reviewed methods to upscale infiltration from the point to the field, hillslope, and grid cell scales of LSMs. Despite the progress that has been made, upscaling of local‐scale infiltration processes to the grid scale used in LSMs is still far from being treated rigorously. We still lack a consistent theoretical framework to predict effective fluxes and parameters that control infiltration in LSMs. Our analysis shows that there is a large variety of approaches used to estimate soil hydraulic properties. Novel, highly resolved soil information at higher resolutions than the grid scale of LSMs may help in better quantifying subgrid variability of key infiltration parameters. Currently, only a few LSMs consider the impact of soil structure on soil hydraulic properties. Finally, we identified several processes not yet considered in LSMs that are known to strongly influence infiltration. Especially, the impact of soil structure on infiltration requires further research. To tackle these challenges and integrate current knowledge on soil processes affecting infiltration processes into LSMs, we advocate a stronger exchange and scientific interaction between the soil and the land surface modeling communities.